Molecular Dynamics Simulation of Silicone Oil Polymerization from Combined QM/MM Modeling - Puhlmann, Pascal; Zahn, Dirk (Polymers, 2024)
We outline a molecular simulation protocol for elucidating the formation of silicone oil from trimethlyl- and dimethlysilanediole precursor mixtures. While the fundamental condensation reactions are effectively described by quantum mechanical calculations, this is combined with molecular mechanics models in order to assess the extended relaxation processes. Within a small series of different precursor mixtures used as starting points, we demonstrate the evolution of the curing degree and heat formation in the course of polymer chain growth. Despite the increasing complexity of the amorphous agglomerate of polymer chains, our approach shows an appealing performance for tackling both elastic and viscous relaxation. Indeed, the finally obtained polymer systems feature 99% curing and thus offer realistic insights into the growth mechanisms of coexisting/competing polymer strands.
CRIS-Team Scopus Importer:2024-07-12
Keywords: molecular dynamics; polymerization mechanisms; silicone